Fluorinated Cell-Penetrating Peptide for Co-Delivering siHIF-1α and Sorafenib to Enhance In Vitro Anti-Tumor Efficacy - Yu Wan; Yuhan Yang; Qiuyue Lai; Wangxia Wang; Mingyu Wu; Shun Feng (MDPI AG, 2023)
Antiangiogenic therapy with sorafenib (SF) alone is ineffective in eradicating tumors, and its long-term application can exacerbate tumor hypoxia, which in turn restricts SF's therapeutic efficacy. Here, a redox-responsive fluorinated peptide (DEN-TAT-PFC) consisting of dendritic poly-lysine, cell-penetrating peptide TAT, and perfluorocarbon was designed and synthesized to co-load siRNA-targeting hypoxia-inducible factors (siHIF-1α) and SF. The unique architecture of the peptide and fluorinated modifications enhanced the siRNA delivery efficiency, including increased siRNA binding, GSH-responsive release, cellular uptake, endosomal escape, and serum resistance. Simultaneously, the DEN-TAT-PFC/SF/siHIF-1α co-delivery system achieved efficient knockdown of HIF-1α at mRNA and protein levels, thus alleviating hypoxia and further substantially reducing VEGF expression. Additionally, the excellent oxygen-carrying ability of DEN-TAT-PFC may facilitate relief of the hypoxic microenvironment. As a result of these synergistic effects, DEN-TAT-PFC/SF/siHIF-1α exhibited considerable anti-tumor cell proliferation and anti-angiogenesis effects. Therefore, DEN-TAT-PFC can be a versatile platform for fabricating fluorine-containing drugs/siRNA complex nano-systems.